Recognizing Nonverbal Distress and Teaching Ethical Empathy in Radiologic Sciences. - Arya, Sanjay (Radiologic Science & Education, 2026)
Silent suffering is a pervasive yet often overlooked challenge in imaging and radiologic sciences, particularly among patients who cannot communicate pain or anxiety verbally. This systematic review synthesized research on ethical empathy, behavioral observation, and validated nonverbal pain assessment tools to guide imaging and radiologic science educators in strengthening students' ability to recognize unspoken distress. Key evidence included validated pain assessment scales, studies on atypical pain communication in autism and dementia, and interdisciplinary findings that highlight how distress can be expressed without words. Illustrative vignettes were incorporated as pedagogical examples rather than empirical data to demonstrate how subtle cues may be interpreted during imaging procedures. Across the literature, a consistent theme emerged that empathy and observational awareness are teachable competencies that require structured integration into imaging and radiologic science curricula. This review offers an educational framework to support the development of ethical empathy and behavioral cue recognition to prepare students and technologists to respond with compassion and accuracy when silence masks suffering.